Use of Quantitative Metagenomics Next-Generation Sequencing to Confirm Fever of Unknown Origin and Infectious Disease - Dong, Yuxin; Gao, Yulei; Chai, Yanfen; Shou, Songtao (Frontiers in Microbiology, 2022)
Fever with a temperature higher than 38.3°C that lasts for at least 3 weeks and lacks a clear diagnosis after 1 week of standard hospital examination and treatment, is called fever of unknown origin (FUO). The main etiologies of FUO are infections, hematological diseases, autoimmune diseases, other noninfectious inflammatory diseases, especially infections. In recent years, the technology of quantitative metagenomics next-generation sequencing (Q-mNGS) has been widely used to detect pathogenic microorganisms, especially in the contribution of rare or new pathogens, such as COVID-19. We introduced a patient who had a 1-month history of fever and clinched leishmaniasis in a non-endemic area by utilizing Q-mNGS. It's necessary to analyze the medical case to comprehend the application value of Q-mNGS in the FUO. The application status of Q-mNGS for the undetermined cause of fever will be discussed further in this article.